Upaya Meningkatkan Ketersediaan Hmt Dan Kapasitas Tampung Ternak Melalui Penanaman Hijauan Sistem Tiga Strata - Danang Biyatmoko (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
The study aims to determine the effect of planting system and cutting age on the level of provision of forage fodder is generated ( fresh , dry matter (DM ) ) and carrying capacity. The research method uses completely randomized factorial design 2 x 4 x 2 replications , using a land plot of 250 m2 per experimental unit . The first factor is the cropping system consists of a type of grass ( R1 ) , TSS models are grass + legume ( R2 ) and the second factor is the age of cutting grass consists of 30 days ( P1 ) , 45 ( P2 ) , 50 ( P3 ) , 60 ( P4 ) , The variables observed is an increase in the production of fresh forage and dry matter (DM ) and carrying capacity. Research indicates that three strata System (TSS) with a superior combination of types of forage legume bushes /shrubs and trees were able to improve the level of production of forage fodder is higher by increased production of fresh forage up to 29.28 % ( R2P3 ) and increased production of dry matter ( DM ) up to 41.39 % higher than the control ( R1P1 ) by planting a single type of grass only. Increased productivity of forages with three strata system ( TSS ) is also able to increase livestock carrying capacity or a stocking rate of 128 AU/ha/year to 165 AU/ha/year